Analisis Model TPS (Think Fair Share) dengan Menggunakan Media Kartu Soal pada Pembelajaran Bahasa Indonesia - Pamela Pamela; Dian Nuzulia Armariena; Susanti Faipri Selegi (Departement of Mathematics Education, 2023)
College students are a new degree for students who have just graduated from high school and are studying in college. New students will live their new lives and be faced with changes both in the lecture environment and where they live, especially for new students who are wandering. In this case, the freshman needs to adjust to be able to live comfortably without pressure in his new environment. . New students need help adjusting to the new environment and world of study. Such assistance can be in the form of social support. The existence of assistance in the form of social support in the process of self-adjustment affects the mental health of new students. This study was conducted to determine the relationship between social support and self-adjustment in wandering freshmen and their effect on mental health.